2008
DOI: 10.4028/www.scientific.net/kem.368-372.1044
|View full text |Cite
|
Sign up to set email alerts
|

Online-Joining of C/SiC-C/SiC via Precursor Infiltration and Pyrolysis Process

Abstract: A novel, online-joining of C/SiC-C/SiC method, precursor infiltration and pyrolysis, was used to obtain high temperature stable joining SiC composition, while joining process was highly consistent with C/SiC preparation process. The compositions of joining ingredients and process parameters were investigated to determine the maximum joining strength of C/SiC-C/SiC at room and high temperatures. The optimum weight ratio of (polycarbosilane/divinyl benzene)/SiC powder is 3/1, and ramping rate of pyrolysis is 2°C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 2 publications
0
1
0
Order By: Relevance
“…With all the combinations involved, the joining process of CyC -SiC is very complicated. Several joining techniques, such as brazing [1,2], diffusion welding [3,4], self-propagating high-temperature synthesis [5], reaction joining process [6,7], etc. have been used to join carbon fibre reinforced carbon matrix composite (CyC), ceramics and ceramic matrix composites.…”
Section: Introductionmentioning
confidence: 99%
“…With all the combinations involved, the joining process of CyC -SiC is very complicated. Several joining techniques, such as brazing [1,2], diffusion welding [3,4], self-propagating high-temperature synthesis [5], reaction joining process [6,7], etc. have been used to join carbon fibre reinforced carbon matrix composite (CyC), ceramics and ceramic matrix composites.…”
Section: Introductionmentioning
confidence: 99%
“…Many joining technologies for C/SiC to metallic systems or C/SiC to C/SiC have been developed, such as brazing [6,7], diffusion welding [8,9], reaction joining process [10,11], PIP/CVI online joining [12,13] and RMI joining process [14,15], yet few papers are published concerning the mechanical joining by introduction of pins or bolts, especially their stripping properties. The mechanical joining with C/SiC pins or bolts for C/SiC composites has some unique advantages such as simplicity, cost-effectiveness, high joining strength and high reliability at moderately high temperature due to similar coefficient of thermal expansion (CET) between the substrates and fasteners.…”
Section: Introductionmentioning
confidence: 99%
“…Efficient joining of C/SiC and C/SiC first requires stable and high strength compositions at high temperature, such as pure SiC or other high temperature ceramics, and accordingly suitable process to prepare joining. Studies showed that the flexural strengths of pure SiC joining components by PCS infiltration and pyrolysis process could remain stable up to 1200°C, but decreased to 60% at 1500°C [15]. Meanwhile, C/SiC components joined only by PIP process showed physical bond not chemical bond, leading to weak joining strength.…”
Section: Introductionmentioning
confidence: 99%